Medical Resource Use and Costs of Treating Sickle Cell-related Vaso-occlusive Crisis Episodes: A Retrospective Claims Study - Nirmish Shah; Menaka Bhor; Lin Xie; Jincy Paulose; Huseyin Yuce (Journal of Health Economics and Outcomes Research, 2020)
# Background The study investigated the economic burden of vaso-occlusive crisis (VOC) among sickle cell disease (SCD) patients, through assessment of overall utilization and costs and costs per VOC episode (regarding the number of VOC episodes and health care setting, respectively).